Elevational Zonation of Carbon Storage and Tree Diversity in Central Himalayan Community Forests for REDD+ and Biodiversity Conservation - Joshi, Nabin Raj; Kshetri, Dipendra; Pant, Gunanand (Nepal Journal of Multidisciplinary Research, 2026)
Background: Climate change, driven largely by anthropogenic greenhouse gas emissions, has placed forest biomass and carbon management at the forefront of global mitigation strategies. In Nepal, there are a total of 23,026 community forestry user groups (CFUGs) covering 20% of the forested area and are critical to rural livelihoods, understanding the interplay between carbon stocks, biodiversity, and elevation is essential for the initiatives like REDD+ carbon financing. Methods: This study investigates aboveground the dynamics of biomass, carbon stock, and tree species diversity along an elevational gradient in Nepal. Data from permanent sample plots in community forests were used and analyzed using R software. Results Results reveal significant altitudinal variation as the biomass stocks were highest at lower elevations (500-1000 masl), peaking at 344.97 t ha⁻¹, while tree density peaked at 1600 ind ha⁻¹ in the 2000-3000 m.a.s.l range. Species dominance shifted from Shorea robusta in lowlands to mixed Quercus and Rhododendron assemblages at mid-elevations, and to conifers species above 2000 m.a.sl. Species dominance shifted from Shorea robusta at low elevations to mixed Quercus-Rhododendron and then conifers at higher elevations. Conclusion: These findings highlight that carbon-biodiversity relationships are not uniform but are mediated by elevation-specific ecological filters. Novelty: This study provides an evidence for designing REDD+ interventions, emphasizing that effective forest carbon policy in Nepal must integrate elevation-specific conservation strategies to synergize climate mitigation with biodiversity co-benefits in the long run.